The Strategic Digitization of ESG-Driven Knowledge Innovation Systems in Global Business Education - Kemrichard, Pattisan (Global journal of Business and Integral Security, 2026)
In the dynamic landscape of 2025, shaped by EU-UK regulatory tensions, Asia’s tech-driven ascent, and global ESG mandates, business schools in the EU, UK, and Asia are pivotal in advancing the digital-green economy. This paper explores the strategic digitization of ESG-driven knowledge innovation systems, leveraging advanced technologies to foster sustainable, inclusive, and innovative business education. Through a comparative case study of leading institutions in the EU (e.g., driven by ESG regulations), the UK (e.g., navigating post-Brexit funding constraints), and Asia (e.g., capitalizing on AI amid U.S.-China tech rivalry), this paper examines the integration of AI-driven analytics, blockchain-secured credentialing, and carbon-neutral digital platforms to transform curricula and operations. These efforts address socioeconomic challenges—enrollment declines, digital divides, and equity demands—while ensuring resilience against digital threats (e.g., cyberattacks fueled by geopolitical tensions) and ecological risks (e.g., resource scarcity). Grounded in the international knowledge-based perspectives and sustainability transitions theory, this paper proposes a transformative framework to integrate ESG-driven digitization, fostering systemic innovation and resilience. The findings highlight how global business schools can lead ESG-aligned change, offering actionable strategies for educators, administrators, and policymakers to navigate 2025’s complexities and position the EU, UK, and Asia as global hubs for sustainable transformation.